Large-eddy simulation of indoor air flow using an efficient finite-volume method. (April 2017) - Kempe, Tobias; Hantsch, Andreas
Abstract: A numerical scheme for the large-eddy simulation of indoor air flows including heat transfer is presented. It is based on a finite-volume discretization of the Navier–Stokes equations for incompressible fluids on Cartesian grids. The governing equations are solved with a projection approach in combination with a direct Poisson solver for the pressure employing Fourier transformations. Complex boundaries are implemented by a variant of the immersed boundary method based on geometrical blocking of the fluid cells. The Boussinesq approximation is used to account for thermal buoyancy effects. The recently developed σ -subgrid scale model is utilized for the modeling of unresolved turbulent scales. Extensive validation of the code is carried out employing numerical and experimental reference data for laminar and turbulent flows in complex geometries including heat transfer. The computational speed is investigated for the flow in a model room including a heat source. It is shown that with the proposed numerical scheme real-time simulations of this configuration can be carried out with high accuracy at moderate numerical effort. Highlights: An efficient scheme for the computation of unsteady indoor air flow is proposed. The representation of complex geometries is realized by an immersed boundary method. Unresolved turbulent subgrid scales are accounted for by the new sigma-model. The resulting algorithm is thoroughly validated by several numerical tests. The method is applied to the real-time simulation of the air flow in a model room.